Evaluating Vacuum and Steam Heat to Eliminate Pinewood Nematodes in Naturally Infested Whole Pine Logs - Eisenback J. D.; Chen Z.; White M. (Journal of Nematology)
Pinewood nematodes threaten forest health and continue to interfere with international trade because they can be spread around the globe via nematode-infested wood. International Standards for Phytosanitary Measure (ISPM-15) requires that all pine wood be treated at 56°C for 30 min to ensure that all pests and pathogens are killed within sawn wood, whereas fumigation with methyl bromide is the currently approved practice and widely used in treating whole logs. A method of treatment that uses less energy and time or does not rely on environmentally damaging gases is urgently needed. Because vacuum with steam has shown promise in treating several different commodities, the purpose of this study was to use it to eradicate pinewood nematodes in whole logs. Three protocols were applied: 1) 48°C for 15 min., 2) 56°C for 30 min., and 3) 60°C for 60 min. The third protocol reduced the population to statistically zero; however, some samples contained at least 1 survivor. Unfortunately, these surviving nematodes increased in number one month after treatment, and one year later, they continued to reproduce in the wood. Therefore, this protocol needs to be further refined to remove pinewood nematodes completely. Explanation of the survival of individual nematodes within whole logs remains a matter for conjecture: 1) certain portions of the wood were somehow insulated from the heat and did not achieve the lethal temperature, and 2) survival stages may be able to survive temperatures that are deadly to the normal life stages.